2014
DOI: 10.7589/2013-05-121
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Psittacine Beak and Feather Disease Virus Spillover Into Wild Critically Endangered Orange-Bellied Parrots (Neophema Chrysogaster)

Abstract: ABSTRACT:We report the recent emergence of a novel beak and feather disease virus (BFDV) genotype in the last remaining wild population of the critically endangered Orange-bellied Parrot (Neophema chrysogaster). This virus poses a significant threat to the recovery of the species and potentially its survival in the wild. We used PCR to detect BFDV in the blood of three psittacine beak and feather disease (PBFD)-affected wild Orange-bellied Parrot fledglings captured as founders for an existing captive breeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 28 publications
3
62
0
3
Order By: Relevance
“…The most notable example is C. lathami, a captive endangered cockatoo species that was likely exposed to wild P. elegans. Similar BFDV spill-over and host-switch events have been shown recently for the endangered orange-bellied parrot (Neophema chrysogaster) (28,29). Our results showed that the partial BFDV genome had phylogenetic structure consistent with the host from which it was sampled with five groups, two of which represent different P. e. flaveolus sampling locations (Fig.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The most notable example is C. lathami, a captive endangered cockatoo species that was likely exposed to wild P. elegans. Similar BFDV spill-over and host-switch events have been shown recently for the endangered orange-bellied parrot (Neophema chrysogaster) (28,29). Our results showed that the partial BFDV genome had phylogenetic structure consistent with the host from which it was sampled with five groups, two of which represent different P. e. flaveolus sampling locations (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…BFDV occurs in many wild and captive parrot populations worldwide, with the potential to cause high mortality (25,26). Accordingly, it is considered a significant conservation threat and has been implicated in parrot declines in Australia and globally (27)(28)(29)(30). BFDV possesses a single-stranded DNA genome of ∼2,000 nucleotides (31).…”
Section: Significancementioning
confidence: 99%
“…To date, there have been six studies of PBFD in wild parrot populations in New Zealand and Australia [2,[23][24][25][26][27], one in the United Kingdom [28], and two in Africa and associated islands in black-cheeked lovebirds and echo parakeets [11,12]. The first evidence of the emergence of PBFD in wild Cape parrot populations in South Africa was reported in 2008, via photographs and field observations.…”
Section: Discussionmentioning
confidence: 96%
“…Psittacine beak and feather disease (PBFD) is a common viral infection that occurs in a wide variety of psittacine birds, globally affecting >60 different species (14). The disease is caused by one of the smallest and simplest viruses belonging to the family Circoviridae , beak and feather disease virus (BFDV), a nonenveloped icosahedral virus with an approximately 2.0-kb circular single-stranded DNA (ssDNA) genome.…”
Section: Genome Announcementmentioning
confidence: 99%